FAKTOR–FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2013-2015) - Wiwik Ardiani, 13.05.52.0258; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2017)
The purpose of this research was to determine the effect size of the Public Accounting Firm (KAP), the size, growth of client companies, financial distress, turnover manajamen audit opinion, audit fee to the auditor switching. This research uses explanatory study, the research describes the relationship between variables. The type or types of relationships in this study is a causal link between one or more variables. Samples were taken by using purposive sampling technique. Samples were 23 companies from 143 companies listed in Indonesia Stock Exchange in 2013-2015, so that the research data was analyzed totaled 69. To analyze the hypothesis used logistic regresion analysis. The results indicate that firm size, growing of client company, financial distress, audit opinion and audit fee not showed effect on auditor switching. Size of client showed negative and significant effect on auditor switching. Change of management showed positive and significant effect on auditor switching.Keywords: Auditor Switching, Firm Size, Size of Client, Growth of Client Company, Financial Distress, Change of Management, Audit Opinion and Audit Fee